(untitled) (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2014)
This article discusses the importance and relevance of textual editing for students and scholars of historical literatures, especially Middle English texts. By surveying the different types of editions necessary for studying Middle English literature, the author argues that in the "digital age," an understanding of The Edition is necessary, not only for the preservation of cultural texts, but also for the contribution and understanding of interpretations fundamental to literary disciplines.